Reprise of the Supershells. Issue Volume 9:Issue S296(2013) (29th January 2014) - Chakraborti, Sayan; Ray, Alak
Abstract: Neutral hydrogen cavities have been detected in the Milky Way for decades and more recently in other nearby star-forming galaxies. It has been suggested that at least a fraction of them may be expanding supershells driven by the combined mechanical feedback from multiple supernovae occurring in an OB association. Yet most extragalactic cavities had neither a demonstrated expansion velocity nor an identified OB association inside them. In this presentation, we will outline how new multiwavelength observations are providing us with systems to test the theory of supershells driven by the mechanical feedback from multiple supernovae. We shall also discuss the consequences of these recent results in the context of supernova feedback, propagating star formation and particle acceleration.